Perbedaan Karakteristik Cedera Olahraga yang dialami Atlet Nomor Lintasan dan Nomor Lapangan pada Invitasi Atletik PASI Papua Menuju PON XXI - Ibrahim, Ibrahim; Kardi, Ipa Sari; Hasan, Baharuddin; Ita, Saharuddin; Lin, Shu-Cheng (Journal of Sport Science and Education, 2023)
The risk of injury in athletes tends to be greater during competition. This study aims to determine the differences in the characteristics of sports injuries that are dominantly experienced by track and field athletes during selection of Papuan athletes for PON XXI 2024. This study uses quantitative research with comparative methods. The population in this study were 409 athletes who participated in the PASI Papua Athletics Invitation. Sampling was chosen purposively among athletes who made it into the final round on track numbers and field numbers which were 264 athletes (track numbers = 185 and field numbers = 79). Data was collected using sports injury identification questionnaire for athletes to find out the characteristics of the dominant sports injuries experienced by athletes. The results showed that the sports injuries experienced by track number athletes were sprain and strains that predominantly occurred in the lower extremities, while injuries experienced by field number athletes were also dominant sprain and strains that occurred in the upper extremities and lower extremities. The results of the independent sample t test wasp=0.804 which indicates no differences in the characteristics of sports injuries experienced by athletics, although there are differences in the location of the injury.